Sistem Pakar Mendiagnosa Penyakit Rheumatoid Arthiritis Dengan Menggunakan Metode Forward Chaining - Reizal Sinaga (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
Artificial intelligence (Artificial Intelligence) is a system that adopts knowledge from experts into an expert system, so that the computer can do as it is done by experts (experts) who act and can assist in providing solutions and making knowledge-based decisions appropriately. Expert systems are computer-based systems that use knowledge, facts, and reasoning techniques in solving problems, and usually can only be solved by an expert in a particular field. Expert systems add value to technology to help doctors diagnose diseases and provide information about types of diseases, as well as symptoms of rheumatoid arthritis Rheumatoid arthritis is an autoimmune disease (a disease that occurs when the body is attacked by the body's immune system and attacks joints) which results in inflammation that causes inflammation and pain. This disease is often affected by hands, feet and knees. Rheumatism can affect the ability to carry out daily activities such as writing, opening bottles, wearing clothes, and carrying things. The application of the forward chaining method in this expert system aims to diagnose rheumatoid arthritis in humans based on the symptoms of rheumatoid arthritis. From the results of this study it can be concluded that the expert system of diagnosing rheumatoid arthritis in humans is expected to help doctors (experts) in providing accurate and precise diagnosis, so that patients know what disease they are suffering from